Estimating location values of agricultural land - Georg Helbing; Zhiwei Shen; Martin Odening; Matthias Ritter (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2017)
"Bodenrichtwerte" reflect the average location value of land plots within a specific area. They constitute an important source of information that contributes to price transparency on land markets. In Germany, "Bodenrichtwerte" are provided by publicly appointed expert groups (Gutachterausschüsse). Using empirical data from Mecklenburg-Western Pomerania between 2013 and 2015, this article examines the relation between 'Bodenrichtwerten' and statistically determined location values. It turns out that 'Bodenrichtwerte' tend to underestimate location values of arable land by 11.5 percent on average. This underestimation can be traced back to the pronounced increase of land prices in the observation period. As an alternative to the expert-based determination of location values, we suggest a nonparametric smoothing procedure that rests on the Propagation-Separation Approach. The application of this data-driven procedure achieves an accuracy comparable to that of official "Bodenrichtwerte" at the one-year ahead prediction of location values without the requirement of expert knowledge.
Keywords: C14; Q15; R39; 330; land value; adaptive weight smoothing; agricultural land markets; propagation-separation approach; PSA